Grain yield and interspecific competition in an oat-common vetch intercropping system at varying sowing density - Wang, Ying; Han, Xue; Zhao, Xingyao; Zhang, Yanli; Qi, Bingjie; Li, Lijun (Frontiers in Plant Science, 2024)
Introduction Oat (Avena nuda L.) and common vetch (Vicia sativa L.) intercropping in the northern regions of China has resulted in substantial production capabilities. However, there is currently a dearth of comprehensive research on whether this intercropping system can enhance productivity through increased sowing densities and underlying interspecies interaction mechanisms. Methods A two-year field experiment was conducted in 2022 and 2023 to investigate the yield, biological efficiency, economic efficiency, and competition indicators of oats and common vetch in a high-density intercropping system. Two cropping patterns (monocropping and intercropping) and five sowing densities (D1: 4.5×106 plants ha-1; D2:5.4×106 plants ha-1; D3:6.3×106 plants ha-1; D4: 7.2×106 plants ha-1; and D5: 8.1×106 plants ha-1) were arranged in a randomized block design. Results At the same sowing density, the intercropped oats exhibited greater grain yield than the monocultures. Increasing the oat sowing density significantly enhanced oat yield, with the D3 level in intercropping showing the highest yield increase, ranging from 30.98% to 31.85%, compared with the monoculture. The common vetch intercropping grain yield was maximized in the D2 treatment. The land equivalent ratio was maximized at the D2 level in both years and was significantly higher than D1, with the land equivalent coefficient, system productivity index, and percentage yield difference suggesting that increasing oat sowing densities improved the productivity of the intercropping system, with the best performance observed at the D2 level. For both years, the proportionate actual yield loss of oat was the highest at the D3 level; significantly surpassing D1, proportionate actual yield loss of common vetch and actual yield loss were the highest at level D2, both significantly surpassing D1. These indicates that appropriate densification contributes to the realization of the advantages of intercropping. With an increased oat sowing density, the economic benefits of the intercropping system were maximized at the D2 and D3 levels. Regarding intercropping competition, oat was the dominant crop under different sowing densities (Aggressivity for oat (AO)>0, relative crowding coefficient for oat (KO)>1, competition ratio for oat (CRO)>1), whereas common vetch was the inferior crop. Compared with the D1 level, the D2 level harmonized the aggressivity, competitive ratio, and relative crowding coefficients of oat and common vetch, significantly increasing crowding coefficient for common vetch (KV) and competition ratio for common vetch by 19.76% to 21.94% and 4.80% to 7.51%, respectively, while reducing KO and CRO. Discussion This result suggests that in the intercropping of common vetch and oat in alpine regions, rational densification can harmonize interspecific competition and thus improve the biological efficiency and economic benefits of intercropping systems.